Early clinical outcomes for treatment of post-thrombotic syndrome and common iliac vein compression with a hybrid Oblique self-expanding nitinol stent - the TOPOS study - Sebastian, Tim; Lichtenberg, Michael; Schlager, Oliver; Jalaie, Houman; de Graaf, Rick; Erbel, Christian; Massmann, Alexander; Schindewolf, Marc; Grigorean, Alexandru; Kucher, Nils (Vasa, 2020)
Background: Physical attributes of conventional stents used in the ilio-caval territory are often unfavorable in the presence of external compression close to the bifurcation. A hybrid oblique stent was developed for the treatment of common iliac vein compression without compromising the contralateral iliac vein inflow. Patients and methods: The ongoing international monitored TOPOS study enrolled 60 patients with post-thrombotic syndrome (PTS) treated with the sinus-Obliquus stent (optimed) and provisional distal stent extension. At 3-month follow-up, patency rates were obtained from duplex ultrasound, and clinical outcomes were assessed by the Villalta score, revised venous severity score (rVCSS), pain intensity score and chronic venous disease quality of life questionnaire (CIVIQ-20). Results: Mean age was 46.6 +/- 14.9 years (68.3 % women). Mean number of implanted stents was 1.9 +/- 0.6; 12 (20 %) patients received the hybrid oblique stent only. Forty-eight (80 %) patients had distal stent extension, and 42 (70 %) had stents below the inguinal ligament. Four (7 %) patients (all with stent extension) developed stent thrombosis. Primary and secondary patency rates at 3 months were 93.1 % (95 %CI 83.3-98.1 %), and 100 % (95 %CI 93.8-100 %), respectively. Improvement in Villalta, rVCSS, CIVIQ-20, and pain intensity score from baseline to 3-month follow-up was 6.9 +/- 1.4 points (95 %CI 4.1-9.8; p < 0.0001), 3.4 +/- 1.0 points (95 %CI 1.3-5.4 points; p < 0.01), 13.6 +/- 2.7 points (95 %CI 8.2-19.0 points; p < 0.0001), and 2.4 +/- 0.5 (95 %CI 1.4-3.3; p < 0.0001), respectively. At follow-up, 38 (63 %) patients were free from the PTS and none developed contralateral deep vein thrombosis. Conclusions: In patients with PTS and common iliac vein compression, treatment with the hybrid oblique stent with provisional stent extension resulted in high patency rates and improvement in PTS severity and quality of life at 3-month. Two-year results of TOPOS will assess the durability of this treatment.
Gesehen am 22.09.2020